Effectiveness of the 21st Century Play Model on Emotional and Social Skills in Thai Early Childhood - สุจริตวงศานนท์ ธนิกา; แสงสัมฤทธิ์ผล วัชรินทร์; ศรีวิไล ทับทิม (Journal of Health Science of Thailand, 2023)
The recent Thai early childhood’s situation showed that emotional and social development was ranked as 2nd least developmental domain along early childhood development standards. Moreover, only a small proportion of children and caregivers played together. The Department of Health, therefore, developed a play model to promote Thai children’s development and skills in 21st century. This study aimed to assess effectiveness of the play model in the contexts of home and early childhood development center on the emotional and social skills in early childhood. It took samples of 415 children aged 3-6 years old in 5 provinces, namely Chiangmai, Ratchaburi, Nonthaburi, Khon Kaen and Nakhon Si Thammarat. The samples were devided into 2 age groups: 399 children aged 3-5 years old using the Thai Emotional Quotient (EQ) Questionnaire for children aged 3-5 years old (brief version) and 263 children aged 4-6 years old using the Strengths and Difficulties Questionnaire (SDQ) to assess the children’s emotional and social skills along their age. In addition, average scores before (pre-scores) and after (post-scores) using the play model in each group were analyzed by Wilcoxon’s test. Also, KruskalWallis test was applied to analyze the pre-scores, post-scores and the difference of pre-scores and post-scores (diff-scores). It was found that, for the children aged 3-5 years old, the post-scores of the Thai EQ Questionnaire significantly increased in control group, home group and early childhood development center group (p<0.05). In the case of the 4-6 year-old children, the post-scores of behavioral problems from the SDQ significantly decreased in control group and home group (p<0.05). In addition, there were significant differences among the 4 groups (the control, the home group, the early childhood development center group, and the mixed home and childhood development center group) (p<0.05). Consequently, the Department of Health should emphasize the widespread use of this play model in order to prepare and promote emotional and social skills in Thai early childhood for 21st century